Pengelolaan Kecemasan Dan Ketidakpastian Komunikasi Virtual: Studi Kasus Kelompok Discord Survivor - Mulya, Muhamad Agam; Nugrahani, Rah Utami; Rochimah, Harris Annisari Indah Nur (eProceedings of Management, 2024)
In Discord Survivor, the members have different cultural backgrounds who did not previously know each other andthere are several members who come from abroad which causes communication barriers to arise. However, withdifferent cultural backgrounds and communication barriers, members of the Discod Survivor group can work togetherand create strategies in playing the Mir4 game. Therefore, this research aims to find out how members who join theDiscord Survivor group can regulate and manage anxiety and uncertainty when interacting caused by differentcultural backgrounds so that these members can interact well. This research uses a qualitative method with a casestudy approach. The results of this research are that informants can manage their anxiety and uncertainty well byusing Gudykunst's theories, namely self-concept, motivation to interact with strangers, reactions to strangers andsocial categories of strangers. Keywords-Discord, anxiety and uncertainty, virtual communication, group communication, Mir4 game.